“A fine wine, better with age”: Circular economy historical roots and influential publications: A bibliometric analysis using Reference Publication Year Spectroscopy (RPYS) - Chedrak, Chembessi; Paulin, Gohoungodji; Rajaonson, Juste (Journal of industrial ecology, 2023)
In this study, we used the Reference Publication Year Spectroscopy (RPYS) method to explore the historical roots and influential publications of circular economy (CE) studies. Unlike traditional literature reviews, this method allows us to analyze frequently cited works over specified years, assisting in tracing the growth of research subjects over time and quantifying the impact of these citations. We reviewed over 8395 publications and 302,377 cited references, ranging from 1521 to 2021. Our study uncovered three distinct periods in the evolution of CE studies: (i) a precursor phase (1521–1988) that presented foundational yet indirectly related ideas; (ii) the “historical roots” (1989–2017) featuring seminal research during 12 notably influential years; and (iii) a recent period (2018–2021) characterized by other highly cited studies. Additionally, we identified several influential publications that have introduced innovative viewpoints and advocated for a systematic approach to CE, shaping the present direction of CE research. Our study not only provides essential context for future studies, helping scholars identify thematic gaps, but also frame their research within the existing body of knowledge, and contribute toward a comprehensive, multifaceted understanding of CE.